Log-domain current-mode quadrature sinusoidal oscillator - Prommee, Pipat; Prapakorn, Nattawit; Swamy, M. N.S. (My University, 2011)
A log-domain current-mode quadrature sinusoidal oscillator based on lossless integrators is presented. The circuit is a direct realization of a first-order differential equation for obtaining the lossy and lossless integrators. Each of the log-domain lossless integrators is realized by using only NPN transistors and a grounded capacitor for achieving low-power and fast response. The proposed oscillator uses two-lossless integrator loop which can be electronically tuned through bias currents. A validated BJT model which is used in SPICE simulation operated from a single power supply as low as 2.5 V. The oscillation frequency is controlled over four decades of frequency. The total harmonic distortions for two-phases QSO (12 MHz) is obtained around 0.93% which enables fully integrated in telecommunication systems. The proposed circuit is also suitable for high-frequency applications. Nonideality studies are included and PSpice simulation results confirm the theoretical results.
Keywords: Electronically-controlled; High-frequency; Log-domain filtering; Low-voltage; Quadrature oscillator